Public health : an action guide to improving health - Walley, John Professor of International Public Health (Oxford University Press, 2010)
Many of the health problems in the developing world can be tackled or prevented through public health measures such as essential health care, improved living conditions, water, sanitation, nutrition, immunization, and the adoption of healthy lifestyles. Public Health is an action guide to improving public/community health, with a particular focus on low- to middle-income countries. It explains public health approaches to developing effective health services and preventive programmes. This Second Edition contains real examples, illustrations and case histories to bring an important subject to life for the reader. The book covers the essential clinical services and preventive programmes — including those for TB, HIV/AIDS, malaria, and diarrhoeal diseases — and the integrated management of childhood and adult illnesses. Practical methods are given for assessing health needs and working with communities to develop health services; and the development of hospital, health centre, and community health services — particularly mother, neonatal, and child health services — are explained. Additionally, gender, social, and economic influences on communities' health are explored.